Purification and Characterization of Xanthine Oxidase from Liver of the Sheep (Ovis Aries) - A.M. Zaahkouk, Samir; A. Darwish, Doaa; M.M. Masoud, Hassan; M. Abdel-Monsef, Mohamed; S. Helmy, Mohamed; S. Esa, Sayed; M. Ghazy, Abdel-Hady; A. Ibrahim, Mahmoud (Journal of Antioxidant Activity, 2019)
Xanthine oxidase is a commercially important enzyme with wide area of medical applications to develop diagnostic kits. Xanthine oxidase was extracted, purified and characterized from sheep liver (SLXO). The purification procedure involved acetone precipitation and chromatography on DEAE-cellulose and Sephacryl S-300 columns. The sheep liver xanthine oxidase was homogeneously purified 31.8 folds with 3.5 U/mg specific activity and 24.1% recovery. SLXO native molecular weight was 150 kDa and on SDS-PAGE appeared as single major band of 75 kDa representing a homodimer protein. Isoelectric focusing of the purified SLXO resolved into two closely related isoforms with pI values of 5.6 and 5.8. The apparent Km for xanthine oxidase at optimum pH 7.6 was found to be 0.9 mM xanthine. FeCl2 and NiCl2 increased the activity of SLXO, while CuCl2 and ZnCl2 were found to be potent inhibitors of the purified enzyme. Allopurinol inhibits SLXO competitively with one binding site on the purified molecule and Ki value of 0.06 mM.
Keywords: Xanthine oxidase; Purification; Characterization; Sheep liver